2019
DOI: 10.1109/tcsi.2018.2881162
|View full text |Cite
|
Sign up to set email alerts
|

ChipNet: Real-Time LiDAR Processing for Drivable Region Segmentation on an FPGA

Abstract: This paper presents a field-programmable gate array (FPGA) design of a segmentation algorithm based on convolutional neural network (CNN) that can process light detection and ranging (LiDAR) data in real-time. For autonomous vehicles, drivable region segmentation is an essential step that sets up the static constraints for planning tasks. Traditional drivable region segmentation algorithms are mostly developed on camera data, so their performance is susceptible to the light conditions and the qualities of road… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…One of the biggest differences when programming an application that runs on a GPU or on a FPGA is the fact that available memory to handle the multiple meta-parameters and weights during CNNs training is more constrained in a FPGA than in a GPU or CPU. Therefore, one of the breakthroughs of this work is the implementation of a simulated quantization step needed to run the training and validation on an FPGA based on a similar approach as the one presented in [10]. As explained there, when using CPU or GPU floating-point operation are used, which create gradients during training.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the biggest differences when programming an application that runs on a GPU or on a FPGA is the fact that available memory to handle the multiple meta-parameters and weights during CNNs training is more constrained in a FPGA than in a GPU or CPU. Therefore, one of the breakthroughs of this work is the implementation of a simulated quantization step needed to run the training and validation on an FPGA based on a similar approach as the one presented in [10]. As explained there, when using CPU or GPU floating-point operation are used, which create gradients during training.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In the method presented in this work a convolutional block similar than the one proposed by [10] has been implemented. One of the main issues of the deep neural network implementation is the so-called vanishing gradient, which means that the gradient of the error used in the back-propagation during training to update the weights gets smaller and smaller on each layer.…”
Section: Convolutional Block: Preparing Data For Fpgamentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, growing research interest is witnessed in automated driving systems (ADS) and advanced driverassistance systems (ADAS). As one of the essential modules, road segmentation perceives the surroundings, detects the drivable region and builds an occupancy map [1] [2] [3] [4]. A drivable region is a connected road surface area that is not occupied by any vehicles, pedestrians, cyclists or other obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Automated driving systems (ADS) and advanced driver assistant systems (ADAS) equipped on intelligent vehicles rely on multiple sensors to perceive their surroundings. In recent research works, LiDAR-based algorithms have shown their advantage on drivable region segmentation [8] [9], object detection [18], and simultaneous localization and mapping [19] [15]. LIDARs are also fused with cameras to improve the accuracy of 3D object detection [2].…”
Section: Introductionmentioning
confidence: 99%